The Gospel of Science - Raymond Downing (Health for All Nations, 2015)
Medical missionaries have always been a part of global health. One of their greatest potential assets as global health workers was that they carried with them a spiritual understanding of life. Although they didn't always realize it, the people they came to serve, especially in Africa, also functioned within a spiritual understanding of life. In the early 19th Century, before medical science had much to offer, some of the medical missionaries were aware of this and recognized that their spirituality had something in common with people in Africa. However, as medical science grew in effectiveness, the role of spirituality in medicine began to diminish, even for medical missionaries themselves. By the early 20th century, their spiritual understandings, while often still very strong in the religious realm, had been replaced by science in the medical realm. How did this come about?